Sustainable tourism and energy security as antecedents of local community’s quality of life in Mabul Island, Malaysia - Siew, Kar Man (2019)
Mabul Island, Semporna, Sabah has received tremendous increase in number of domestic and international visitors since year 2011. The objective of the Malaysian government’s effort as formulated in Malaysian 11th Plan in achieving sustainable improvement in people’s quality of life, sustainable development in tourism industry and energy security should not be overlooked. It is also indicated in the National Ecotourism Plan (NEP) 2016-2025 that more attention is being placed towards the social science studies especially in relation to the local community development. The purpose of this study is to determine the perceived quality of life of an offshore island community and their awareness on both sustainable tourism impacts and perception on energy security. Specifically, the research objectives are i) to determine the socio demographic characteristics of community in Mabul Island; ii) to determine the Mabul Island community’s perception of quality of life; iii) to determine the factors influencing community’s perceived quality of life in Mabul Island. Face to face interview sessions were conducted among local community residing in Mabul Island. A total of 504 useable questionnaires were collected and used for the analysis. The study has found that Mabul Island community’s perception of quality of life is high with an average of 4.5 out of a 5-point Likert scale. The findings also show that eleven variables are significantly influencing the community’s perceived quality of life in Mabul Island. The factors are ethnicity (Suluk, Bajau and Bajau Suluk) with significant value of 0.768, 0.762 and 0.814 respectively, occupation (tourism service, business owner and fishermen) with significant value of -0.239,-0.176 and -0.200 respectively, education level (illiterate and primary school) with significant value of -0.190 and -0.212 respectively, perceived sustainable tourism economic impacts with significant value of 0.063, perceived sustainable tourism social impacts with significant value of 0.123, and perceived energy security with significant value of 0.062. Several recommendations are highlighted with the hope that the current findings add substantially to the understanding of the importance of sustainable development to quality of life, tourism industry and also energy development. This study also hopes that it can assist the concerned parties especially the government to further improve the life quality of rural community through better policy planning.